On Distributive Properties of Some Two-Place Causative Verbs in Lithuanian and English - Карпувене, Г. (Kalbotyra, 1976)
The aim of the paper is the comparative analysis of semantic structure of some two-place causative verbs in Lithuanian and English. The attention is focused on distributive properties of these verbs.